PM’s visit spurs development progress in UMP Pekan Campus - UMP, PNC
Prime Minister Yang Amat Berhormat Dato’ Sri Mohd Najib Tun Razak made an official visit to Universiti Malaysia Pahang (UMP) permanent campus in Kuala Pahang on March 12, 2011.